T cell subsets and disease progression after total lymphoid irradiation in chronic progressive multiple sclerosis. Issue 7 (July 1988) - Troiano, R; Devereux, C; Oleske, J; Denny, T; Hafstein, M; Zito, G; Rohowski-Kochan, C; Dowling, P C; Cook, S D
Abstract : T lymphocyte subset percentages were determined in 16 total lymphoid irradiation (TLI) treated and 18 sham treated control patients with chronic progressive multiple sclerosis. During the first year after treatment, the ratio of T helper/inducer to T suppressor/cytotoxic cells (Th/Ts ratio) was significantly higher in sham treated multiple sclerosis patients who worsened clinically compared with TLI treated and sham treated multiple sclerosis patients who remained clinically stable. TLI caused a fall in the percentage of T helper cells in treated patients, while the percentage of T suppressor cells remained stable during the first year after treatment. In contrast, the percentage of T suppressor cells fell in sham treated multiple sclerosis patients who worsened clinically.